Analisis Kelayakan Proyek Sistem Informasi Persediaan - Shintia, Novi; Mantala, Ronny (P3M Politeknik Negeri Banjarmasin, 2019)
Abstract - For profit-oriented and non-profit companies, the profit element is the main focus, it is understandable considering that the resources invested are not small. An information system developed must also take into account the costs and benefits for the organization. This article examines the level of feasibility of inventory information system projects in the Family Collection in terms of technical, operational, legal and economic aspects. From the feasibility test on the information system project it was found that the technical, operational and legal feasibility showed a positive thing. The economic feasibility test with a project length of 3 years on several quantitative testing methods also shows a positive thing; payback period = 1.6 years, ROI of 65%, NPV> 0, and IRR of 37. 44%. From this study it can be concluded that the inventory information system development project in the Family Collection has the feasibility to be carried out because it is supported by technical, operational, legal and economic feasibility factors. The contribution of this research can at least provide input for system analysts in analyzing the feasibility of information system projects on similar business objects. Keywords - Information System Feasibility Analysis, Cost-Benefit Analysis, Payback Period, ROI, NPV, IRR.